2018
DOI: 10.3390/a12010007
|View full text |Cite
|
Sign up to set email alerts
|

Salt and Pepper Noise Removal with Multi-Class Dictionary Learning and L0 Norm Regularizations

Abstract: Images may be corrupted by salt and pepper impulse noise during image acquisitions or transmissions. Although promising denoising performances have been recently obtained with sparse representations, how to restore high-quality images remains challenging and open. In this work, image sparsity is enhanced with a fast multiclass dictionary learning, and then both the sparsity regularization and robust data fidelity are formulated as minimizations of L0-L0 norms for salt and pepper impulse noise removal. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The algorithm has high image restoration power to produce restored images with a high PSNR value. Guo et al [69] have introduced a novel algorithm to enhance image sparsity to help remove salt and pepper noise removal with a fast multiclass dictionary learning, and then both the sparsity regularization and robust data fidelity are formulated as minimizations of 0 − 0 norm for impulse noise removal. Additionally, a numerical algorithm of modified alternating direction minimization is derived to solve the proposed denoising model.…”
Section: A Methodologies Of Dictionary Learning Models (Impulse Noise)mentioning
confidence: 99%
“…The algorithm has high image restoration power to produce restored images with a high PSNR value. Guo et al [69] have introduced a novel algorithm to enhance image sparsity to help remove salt and pepper noise removal with a fast multiclass dictionary learning, and then both the sparsity regularization and robust data fidelity are formulated as minimizations of 0 − 0 norm for impulse noise removal. Additionally, a numerical algorithm of modified alternating direction minimization is derived to solve the proposed denoising model.…”
Section: A Methodologies Of Dictionary Learning Models (Impulse Noise)mentioning
confidence: 99%
“…Figure 2(e) also exhibits high sparsity. We constrain this sparsity of the stripe noise using the L0-norm which describes the sparsity extremely well [ 21 , 22 ]. Therefore, the established regular term is as follows: where d y denotes the convolution operator in the vertical direction, N n denotes stripe noises in the n th -level vertical component.…”
Section: Algorithm Compositionmentioning
confidence: 99%
“…Sample reduction solves the enormous amount of data problem by selecting only representation samples to be the training sets [298]- [300]. Dimension reduction such as feature engineering [301]- [313], feature learning [33], [314]- [318], and feature selection [319]- [326] [151], [327]- [335].…”
Section: Curse Of Dimensionalitymentioning
confidence: 99%
“…-norm minimization (eqn. (1.2)) has been successfully used for background subtraction[153] and viewpoint classification for anomaly detection[5], signal denoising and error correction[147]-[151], superresolution reconstruction[152],[420], background subtraction[153] and dictionary learning[153]. Similar to the works in[4], the theoretical workpresented has shown that the -norm minimization (eqn.…”
mentioning
confidence: 93%
See 1 more Smart Citation